Hepatic Critical Care (Springer International Publishing, 2018)
This book focuses on the critical care of the patient with acute, acute on chronic and chronic liver failure as well as the peri-operative care of the patient with liver transplantation. Each of these disease processes is unique in pathophysiological manifestations, underpinnings of physiology and treatment options. Patients with acute, chronic or acute on chronic liver failure are a growing fraction of ICU admissions. Hepatic Critical Care serves as the essential reference for both practicing intensivists at community hospitals and tertiary referral centers. This textbook is also targeted towards trainees specifically interested in taking care of patients with liver disease and liver transplantation. .